Localized population divergence of vervet monkeys (Chlorocebus spp.) in South Africa: Evidence from mtDNA. Issue 1 (12th August 2015) - Turner, Trudy R.; Coetzer, Willem G.; Schmitt, Christopher A.; Lorenz, Joseph G.; Freimer, Nelson B.; Grobler, J. Paul
ABSTRACT: Objective: Vervet monkeys are common in most tree‐rich areas of South Africa, but their absence from grassland and semi‐desert areas of the country suggest potentially restricted and mosaic local population patterns that may have relevance to local phenotype patterns and selection. A portion of the mitochondrial DNA control region was sequenced to study patterns of genetic differentiation. Methods: DNA was extracted, and mitochondrial DNA sequences were obtained from 101 vervet monkeys at 15 localities, which represent both an extensive (widely across the distribution range) and intensive (more than one troop at most of the localities) sampling strategy. Analyses utilized Arlequin 3.1, MEGA 6, BEAST v1.5.2, and Network V3.6.1. Results: The dataset contained 26 distinct haplotypes, with six populations fixed for single haplotypes. Pairwise P ‐distance among population pairs showed significant differentiation among most population pairs, but with nonsignificant differences among populations within some regions. Populations were grouped into three broad clusters in a maximum likelihood phylogenetic tree and a haplotype network. These clusters correspond to i) north‐western, northern, and north‐eastern parts of the distribution range as well as the northern coastal belt; ii) central areas of the country; and iii) southern part of the Indian Ocean coastal belt and adjacent inland areas. Conclusions: Apparent patterns of genetic structure correspond to current and past distribution of suitable habitat, geographic barriers to gene flow, geographic distance, and female philopatry. However, further work on nuclear markers and other genomic data are necessary to confirm these results. Am J Phys Anthropol 159:17–30, 2016. © 2015 Wiley Periodicals, Inc.